2002
DOI: 10.1080/00221300209602107
|View full text |Cite
|
Sign up to set email alerts
|

Up or Down: The Influence of Upcoming Reinforcement on Consummatory and Operant Behavior

Abstract: Research has shown that animal subjects that are given a chance to consume a low-valued substance will consume less of it if a high-valued substance will soon be available than they would if the low-valued substance were to remain available (negative consummatory contrast). Research has also shown that subjects that lever press for a low-valued reinforcer will press the lever more often for that reinforcer if they will soon be able to lever press for a high-valued reinforcer than they would if they continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This ‘Crespi Effect’ relied on a between group comparison with controls not experiencing an alteration of outcome value. Recent work on incentive contrast has found the effect to be more complicated than originally proposed (Binkley et al, 2014; Nyland et al, 2012; Ortega et al, 2011; King et al, 2002). Based on the complex but crucial nature of relative reward processing, it is vital that new paradigms are developed and explored to clarify interactions and overcome obstacles in understanding factors involved in incentive contrast as well as similar effects on behavior (Webber et al, 2011; Cromwell, 2010; Cromwell et al, 2005; Watanabe et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This ‘Crespi Effect’ relied on a between group comparison with controls not experiencing an alteration of outcome value. Recent work on incentive contrast has found the effect to be more complicated than originally proposed (Binkley et al, 2014; Nyland et al, 2012; Ortega et al, 2011; King et al, 2002). Based on the complex but crucial nature of relative reward processing, it is vital that new paradigms are developed and explored to clarify interactions and overcome obstacles in understanding factors involved in incentive contrast as well as similar effects on behavior (Webber et al, 2011; Cromwell, 2010; Cromwell et al, 2005; Watanabe et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
“…Another complicating issue is the existence of different forms of ‘contrast’ that can involve generalization among outcomes and relative effects that are opposite to traditional contrast effects (Weatherly et al, 2001; King et al, 2002; Lupfer-Johnson et al, 2010). For example, positive induction has been proposed as an opponent effect to anticipatory negative contrast (Weatherly et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The rats that pressed levers, however, collected and consumed the sucrose in the different halves of the session from the same trough, and induction was observed. Similar outcomes occurred in King et al (2002). In fact, in all of the studies from our laboratory that have reported positive induction, the lesser valued reinforcer in the first half of the session has been delivered to the same place as the upcoming, more valued substance.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, Flaherty and Rowan (1985) showed that rats given 3-min free access to a 0.15% saccharin solution consumed less of it if the upcoming 3-min period would allow access to a 32% sucrose solution rather than continued access to 0.15% saccharin. King, Brandt, and Weatherly (2002) demonstrated that the same subjects would display consummatory contrast and induction when responding for the same substances. In the first phase of their Experiment 3, rats were given 3-min periods of free access to 1% liquid sucrose, followed after a 15-s delay by 3-min periods of free access to 1% sucrose, 32% sucrose, or 45-mg food pellets, in different conditions.…”
mentioning
confidence: 96%
See 1 more Smart Citation